Negotiating care in organizational borderlands: a grounded theory of inter-organizational collaboration in coordination of care - Ann-Therese Hedqvist; Catharina Lindberg; Heidi Hagerman; Ann Svensson; Mirjam Ekstedt (BMC, 2024)
Abstract Background Although coordination of care and integrated care models aim to enhance patient satisfaction and perceived care quality, evidence regarding their practical implementation remains scarce. Understanding the nuances of collaboration across care providers to achieve effective coordination of care is imperative for seamless care integration. The aim of this study was to construct a grounded theory of how inter-organizational collaboration is performed to support coordination of care for patients with complex care needs. Methods A qualitative design with a constructivist grounded theory approach was applied. In total, 86 participants with diverse backgrounds were recruited across multiple care settings, including hospitals, ambulance services, primary care centers, municipal home healthcare and home care services. The grounded theory was developed iteratively, based on a combination of observations and interviews, and using constant comparative analysis. Results Coordination of care, a complex process that occurs across interconnected healthcare organizations, is manifested as "Negotiating care in organizational borderlands." Care coordination evolves through a spectrum of inter-organizational collaboration, ranging from "Dividing care by disease-specific expertise" to "Establishing paths for collaboration" and ultimately "Co-constructing a comprehensive whole." These categories highlight the challenges of coordinating care across both professional and organizational boundaries. In the multifaceted healthcare landscape, effective care coordination occurs when healthcare professionals actively bridge the divides, leveraging their collective expertise. Importantly, organizational boundaries may serve a purpose and should not be dissolved to facilitate effective care coordination. Conclusions The key to effective care coordination lies in robust inter-organizational collaboration. Even when patients receive integrated care, healthcare professionals may have fragmented roles. This research emphasizes the importance of clearly defined lines of accountability, reinforcing mutual responsibility and facilitating bridging of professional and organizational boundaries. Healthcare professionals and policymakers can use these insights to effectively utilize inter-organizational collaboration in supporting care coordination for patients with complex care needs.